Dimensionering av Jumkils nya skolas energisystem - Andersson, Frida; Carlsson, Johanna; Hane, Linnéa; Larsson, Jesper; Lindén Magnusson, Josephine; Olofsson, Hanna; Robertsson, Richard; Roos, Pontus; Wänlund, Jessica (2018)
The purpose of this study is to develop a modern and energy efficient system solution for a school in Jumkil, combining solar power, battery storage and geothermal heat pump system. By using models, simulations and available literature the study examines the dimensions of the included components for optimal coverage of the schools energy demand. The type of solar cells used is monochrystalline silicon solar cells and from an economical point of view, the installed effect should be 55 kWp. For such a solution the optimal battery capacity is 60 kWh and the battery technique used is vanadium redox flow battery. The vanadium redox flow battery technique is safe, have a long lifetime as well as a high depth of discharge. Implementing a smaller photovoltaic plant of 22 kWp reduces the need of battery capacity to 20 kWh. The battery is used for several applications, for example storage of the excess solar production and reducing the power peaks to eliminate expensive charge. An inverter heat pump of 79 kW is installed to cover the heat demand. The study also shows that a geothermal automatically controlled heat pump combined with floor heating is the best combination to reduce electricity costs annually. In interaction with the self-produced power and the vanadium redox flow battery the system allows the school to reduce their electricity consumption and thus the need of buying power from the grid decreases.